Faktor-Faktor yang Mempengaruhi Onset Laktasi pada Ibu Post Partum di Rumah Sakit Ibu dan Anak Puri Bunda Malang - Dina Yusi Ayu Pramesi; Afnani Toyibah; Reni Wahyu (Poltekkes Kemenkes Malang, 2021)
Exclusive breastfeeding is still very far from the national target of 80 percent. Infants who do not get breast milk will have an increased risk of respiratory infections, gastrointestinal infections, interfere with growth and development and poor body defense. Several studies have shown that the onset of lactation is one of the success factors of exclusive breastfeeding. Lactation onset is the mother perception when the breast feels hard, full or heavy and until milk or colostrum comes out. This study aims to determine the factors that influence the onset of lactation in post partum mothers, namely parity, labor and anxiety. This research is an analytical study with cross sectional approach, the sample in this study was 74 post partum mothers using purposive sampling method. Data collection using the lactation onset questionnaire and the Hamilton Rating Skale for Anxiety or HRS A questionnaire. Data analysis was carried out univariately and bivariately using the Chi Square test which showed that all factors namely parity, delivery methods and anxiety can influence the onset of lactation in post partum mothers. The parity factor was found to be p equal 0.023, the labor method was p equal 0.037, and the anxiety factor was p equal 0.002. The conclusion based on the results of the study is that multiparous mothers experience lactation onset faster than primiparous mothers, mothers with normal labor have lactation onset faster than mothers with cesarean delivery and mothers who experience anxiety will be slower in lactation onset compared to mothers who are not anxious. With the known influence of parity, delivery methods and anxiety with lactation onset is expected to increase breastfeeding for infants in RSIA Puri Bunda Malang.